Pelatihan Manajemen Aset Kampung Bagi Aparatur Kantor Pemerintahan Kampung Holtekamp Distrik Muara Tami Kota Jayapura - Kambuaya, Maylen K.P.; Sesa, Pascalina V.S.; Patma, Kurniawan; Rofingatun, Siti (UNIVERSITAS CENDERAWASIH, 2024)
The Minister of Home Affairs Regulation Number 1 of 2016 addresses village asset management, encompassing village wealth, properties acquired via village funds, grants, donations, agreements, laws, cooperative efforts, and other legal means. Research by Dandi D. Mnumumes (2022) reveals that Holtekamp Village’s asset management report does not comply with this regulation at any stage. Consequently, Asset Management training was provided to the Holtekamp Village Government Apparatus in Jayapura City. This training aimed to enhance the knowledge and awareness of village office staff and the community about the importance of managing village assets to boost community welfare. The training was conducted in person and comprised three sessions: the first session covered Asset Management material, the second involved a discussion, and the third included distributing questionnaires to evaluate asset management and optimization in Holtekamp Village. The feedback from the participants, a crucial part of the process, indicated an improved understanding of proper village asset management. This is crucial because village assets significantly contribute to village revenues, which are vital for government functions and support the sustainable development of villages. Such management is essential for driving villages toward becoming self-reliant communities. Keywords: Village asset management, Holtekamp Village Government Office apparatus